Hubungan Antara Kepercayaan Diri Dengan Perilaku Merokok Siswa Di Sman 5 Medan - Bernando Petrus; Laili Alfita (Jouska: Jurnal Ilmiah Psikologi, 2022)
This article aims to determine the correlation between self-confidence and smoking behavior of students at SMAN 5 Medan. The problem is that there is a negative relationship between the relationship between self-confidence and smoking behavior at SMAN 5 Medan. The sampling technique in this study was purposive sampling with a sample of 60 people. The data collected using a Likert scale through a self-confidence scale consisting of aspects of self-confidence according to Lauster (2014) namely self-confidence, optimism, objective, responsible, rational and realistic, also using a smoking behavior scale which is based on theory. Sarafino is modeling, peer pressure, smoker image and personal character. And analyzed quantitatively with the technique of production moment correlation. This study concludes that there is a negative relationship between self-confidence and smoking behavior. This result is evidenced by the correlation coefficient Rxy = 0.384, p = 0.000 means p 0.010. The results are based on the calculation of the Hypothetical and empirical mean value, it is known that SD = 12,648. The hypothetical self-confidence is 45.00 and the empirical mean is 52.934 is categorized as moderate and for smoking behavior SD = 10.352, where the hypothetical is 60.00 and the empirical mean is 84,467 is high. Based on the results of the study, the weight of the effective contribution of X to Y was 14.80% declared accepted.